Ionic Conductivity of the Li6PS5Cl0.5Br0.5 Argyrodite Electrolyte at Different Operating and Pelletizing Pressures and Temperatures - Joshua Dunham; Joshua Carfang; Chan-Yeop Yu; Raziyeh Ghahremani; Rashid Farahati; Siamak Farhad (Energies, 2023)
All-solid-state lithium batteries (ASSLBs) using argyrodite electrolyte materials have shown promise for applications in electric vehicles (EVs). However, understanding the effects of processing parameters on the ionic conductivity of these electrolytes is crucial for optimizing battery performance and manufacturing methods. This study investigates the influence of electrolyte operating temperature, electrolyte operating pressure, electrolyte pelletization pressure, and electrolyte pelletizing temperature on the ionic conductivity of the Li6PS5Cl0.5Br0.5 argyrodite electrolyte (AmpceraTM, D50 = 10 µm). A specially designed test cell is employed for the experimental measurements, allowing for controlled pelletization and testing within the same tooling. The results demonstrate the significant impact of the four parameters on the ionic conductivity of the argyrodite electrolyte. The electrolyte operating temperature has a more pronounced effect than operating pressure, and pelletizing temperature exerts a greater influence than pelletizing pressure. This study provides graphs that aid in understanding the interplay between these parameters and achieving desired conductivity values. It also establishes a baseline for the maximum pelletizing temperature before undesirable degradation of the electrolyte occurs. By manipulating the pelletizing pressure, operating pressure, and pelletizing temperature, battery engineers can achieve the desired conductivity for specific applications. The findings emphasize the need to consider operating conditions to ensure satisfactory low-temperature performance, particularly for EVs. Overall, this study provides valuable insights into processing and operating conditions for ASSLBs utilizing the Li6PS5Cl0.5Br0.5 argyrodite electrolyte.